2022
DOI: 10.1088/1755-1315/974/1/012129
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod diversity in ramie (Boehmeria nivea (L.) Gaudich) plantation

Abstract: Understanding the diversity of arthropods in a crop ecosystem could be used as a basis to develop pest management in the crop cultivation. The insect pest management system for ramie has not been developed intensively in Indonesia. Therefore, this study aimed to evaluate the diversity of arthropods associated with ramie plantation. The research was done using a survey method in ramie plantations at Wonosobo, Central Java from August 2020 to March 2021. The survey method applied was direct and indirect observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For the conditions of Siberia, it is important to use early ripening hybrids of the intensive type, which have high productivity in combination with a balanced amino acid composition of proteins [11][12]. It has been shown that elements of production technology affect the quality of corn grain by increasing the concentration of essential amino acids in proteins [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For the conditions of Siberia, it is important to use early ripening hybrids of the intensive type, which have high productivity in combination with a balanced amino acid composition of proteins [11][12]. It has been shown that elements of production technology affect the quality of corn grain by increasing the concentration of essential amino acids in proteins [13][14].…”
Section: Introductionmentioning
confidence: 99%